HUBUNGAN POLA MAKAN DAN KUALITAS TIDUR SAAT PUASA TERHADAP KEJADIAN GERD PADA MAHASISWA FAKULTAS KESEHATAN UNIVERSITAS MUHAMMADIYAH GRESIK - Fauzana, Anika; Suprihatinigrum, Dwi Novri; Rahma, Amalia (Ghidza Media Jurnal, 2024)
ABSTRACT Gastroesophageal Reflux Disease (GERD) is a chronic disease caused by inappropriate consumption patterns and lifestyle. Fasting is believed to reduce the symptoms of GERD that occur because when fasting your diet is better maintained. This study aims to determine the relationship between eating patterns and sleep quality during fasting on the incidence of GERD in students at the Faculty of Health, Muhammadiyah University of Gresik. This research involved 81 respondents obtained from a non-probability sampling technique using a purposive sampling method. Data was obtained from filling out the 3×24 hour Recall questionnaire, FFQ, PSQI, GERD-Q, and eating and sleeping intervals. The research results showed that 34.6% of respondents experienced GERD, while 65.4% of respondents did not experience GERD. The Spearman correlation test results showed r = 0.239 for the correlation of energy intake with GERD, r = 0.268 for the correlation of fat intake with GERD, r = 0.276 for the correlation of spicy food consumption with GERD, r = 0.275 for the correlation of high-fat food consumption with GERD, and r = 0.293 for the correlation between eating and sleeping distance with GERD. From the research results, it can be concluded that there is a significant relationship with a weak correlation level between energy intake, fat intake, spicy food, high fat food and eating and sleeping intervals with GERD (p < 0.05).